The associations between religiosity, socioeconomic status, and subjective wellbeing between developing and developed countries - Lau, Samuel Miang Yeow (Nanyang Technological University, 2023)
Recent research showed that the associations between lower socioeconomic status and decreased subjective wellbeing were largest in developed countries, rather than developing ones. The decrease in religiosity in developed countries, based on the secularisation thesis, could be a possible explanation for this phenomenon. Thus, this study explored the associations between religious practice and belief, socioeconomic status, and country development on subjective wellbeing. I conducted multilevel modelling utilising the publicly available World Values Survey dataset, consisting of 94,278 participants from 62 countries after filtering. I found that 1) religiosity and socioeconomic status were positively associated with subjective wellbeing, 2) individuals in developed countries experienced significantly greater subjective wellbeing when they perceived themselves to be in a higher, rather than lower, social class, compared to individuals in the same perceived social class in developing countries, and 3) individuals with higher religious practice and belief in lower social classes reported higher subjective wellbeing than their non-religious counterparts in the same socioeconomic status; this effect was not found to differ between developing and developed countries. Based on these findings, I made recommendations that subjective wellbeing can be enhanced by religious support worldwide, and developed countries could adopt mindfulness-based interventions to alter societal values that pursue intrinsic, rather than extrinsic, goals, and contentment over material achievement. Keywords: